Analisis Biaya Pengurasan Sedimentasi pada Kolam Pengendap Lumpur di PT Bukit Asam Tbk Unit Pertambangan Tanjung Enim Sumatera Selatan - Gumanti, Suhardiman; Julisti, Rena; Yovanda, Ridho (Journal of Comprehensive Science, 2024)
PT Bukit Asam is one of the companies engaged in the coal mining sector which is located in Tanjung Enim, South Sematra. The mining system applied in exploiting coal is open pit mining which produces water called acid mine water (AAT), one of the components of the AAT problem. namely total suspended solid (TSS). At PT Bukit Asam, Bangko Barat, there are several KPLs that are still in use. KPLs that are continuously supplied with mining water certainly produce a negative impact, namely silting. The aim of this research is to analyze the cost of dewatering sedimentation in mud settling ponds. The method used in this research is to use field visits and direct observations. The shallowing itself is caused by rain factors and the long deposition time. To prevent silting, draining is carried out using an excavator and loading of the material using a dump truck. Draining activities in February amounted to IDR 185,634,400.00 handling the mud settling ponds also using chemicals or control methods which are useful for settling mud particles so that the draining process at the KPL runs quickly.